Ángel Pazos-López y Ana María Cuesta Sánchez (eds.), Las imágenes de los animales fantásticos en la Edad Media. Gijón: Ediciones Trea, 2022, 616 p. ISBN: 978-84-19525-21-5. - Nodar Fernández, Victoriano (De Medio Aevo, 2024)
un